Usage of solar and wind energy for hot water supply of country (cottage) house in natural conditions of absheron - Salmanova, Firuza Aziz; Rzayev, Parviz Fikri; Yusupov, Igor Mevlud; Velizade, Ismail Elshen (Eastern-European Journal of Enterprise Technologies, 2016)
The calculations show that it is becoming possible to generate the powers of wind device and solar water heater approximately up to 4 kVt due to the use of the offered system SWH+WED. Using the developed system for the purposes makes possible, first, to improve the ecological situation in the region for the summer period and secondly, to reduce fuel and electric energy consumption used in the region standard conditions. Usage of solar and wind energy may save fuel, heavy fuel oil and electric power up to the average 15–20 % percent in natural conditions of Absheron. These data were found by us on analyses of common records from statistics of corresponding departments and institutes. The authors have offered and build practically for the first time the SWH + WED system considered for heating the country (cottage) houses in native conditions of Absheron where solar radiation intensity and wind speed are approximately 500–600 Vt/m2 7–10 m/sec. respectively in the studied period of the year. It may use the developed system effectively for the hot water supply to the residents of this Region. To our opinion, that may save heavy fuel oil and electric power up to 30–35 % percent taking into account negative data of the departments corresponding.